XPS investigation of Si3N4/SiC nanocomposites prepared using a commercial polymer - Oh, YS; Cho, WS; Kim, CS; Lim, DS; Cheong, DS (AMER CERAMIC SOC, 1999)
We have synthesized Si3N4/SiC nanocomposites using a commercial polymer. Formation behavior of SiC nanoparticles has been studied using X-ray photoelectron spectroscopy (XPS). Based on the XPS results, we concluded that SiC nanoparticles were formed by a chemical reaction of Si provided from Si3N4 with free carbon obtained by pyrolysis of a polymer around 1300 degrees C. The presence of CNx compounds in samples processed in an Ar atmosphere supported our explanation.
Keywords: SILICON-CARBIDE; FABRICATION; TEMPERATURE; SURFACES; LASER